SIMPLE RENTAL FLATS FOR THE LOWER AND MIDDLE CLASS IN THE CITY OF BANDUNG - Dianna Astrid Hertoety (Sean Institute, 2022)
The city of Bandung has a lot of potential in terms of economy, tourism and for-profit and non-profit institutions so that many people migrate to the city of Bandung. This matter is certainly good in helping to improve the regional economy, but this also triggers the problems that exist at this time where the need for land in the city of Bandung is very high with its availability so low that land prices become expensive and the birth of slum problems in the city of Bandung which has an impact on public health and the surrounding environment. This can be handled by the provision of vertical housing or flats. Basically, flats are built due to the impact of the development of urban areas that are so fast that the increase in population density, building density, decreased income of the population, degradation of infrastructure quality and narrowing of residential land (Bramley, 2010). The design process of flats is associated with a green architecture approach with the aim of reducing the negative impacts that buildings have on the environment and providing housing with the fulfillment of healthy, comfortable, safe and good criteria for the environment.